Produção IN VITRO de Embriões Bovinos. - Vilanova, Camila Sousa (Universidade Federal do Tocantins, 2023)
All these processes are followed from the Maturation after the oocytes are aspirated from donor cows in the rural properties of clients of the company and brought to the laboratory, until the moment of packaging of the same ones for the transfer of embryos in receiving cows. The activities developed in the company In Vitro Brazil S / A had as main objective laboratory practices in the in vitro production of bovine embryos. In the laboratory are performed procedures such as: Maturation of bovine oocytes in maturation medium, In vitro fertilization of mature oocytes, Culture of embryos in specific medium, Cleavage, Prediction and Packaging for the transfer of embryos. The activities carried out improved the understanding of In Vitro Production of Embryos (PIVE), contributing to professional training.